Implications of Cultural Capital in Women’s Higher Education Participation and Social Mobility - Muhammad Uzair-ul-Hassan، Iram Parveen ، Sobia Saleem (PJE, 2023)
Equality of opportunity in higher education participation is a basic right of people in a society that leads to their social mobility in the long run. Benadusi (2002) endorsed Bourdieu’s explanations that cultural capital acts as an empowering force that predetermines equality/inequality of educational opportunity of people in a society. The study, thus, aimed to explore cultural capital as means of participation in higher education and eventually social mobility of women۔